Manual técnico: Plagas de la quinua, manejo integrado para agricultura sostenible y resiliente - Delgado Mamani, Pedro; Goyzueta Hancco, Washington; Castro Hancco, Jhon; Loza del Carpio, Alfredo; Chura Parisaca, Eusebio (Instituto Nacional de Innovación Agraria, 2020)
92 Páginas